Analysis of panel data - Hsiao, Cheng (Cambridge: Cambridge University Press, 1989)
This book reviews the basic econometric methods that have been used to analyze panel data - in other words, data collected by observing a number of individuals over time. Empirical examples are provided to illustrate the theoretical discussion as well as to indicate areas of research where panel data might be useful.
Includes Index.
Keywords: Analysis of variance; Econometrics